Δημιουργία Εκπαιδευτικού Υλικού για Εξ αποστάσεως Εκπαίδευση Νοσηλευτών, Σχετικά με τη Διαχείριση Ασθενών με Σακχαρώδη Διαβήτη. - Αργυρόπουλος, Θεόδωρος; Χρονοπούλου, Ιωάννα (Nosileftiki)
Introduction: From the review of Greek and international literature, there is a modern trend in distance e-learning. and Nurses with the use of IT technologies. However, this training requires appropriate educational material and selected teaching content. Purpose: The purpose of this review is to investigate the methodology for the development of educational material for the distance education of nurses in the care of patients with diabetes mellitus. Material and Method: A bibliographic review of the international bibliography was searched to search for articles in electronic databases (google scholar, pup med) with appropriate indexing words. Searched articles were published in Greek or English in reputable journals published after 2000. The review period was three months and related to distance learning, nursing relationship with new technologies, diabetes and quality teacher education material. In particular, content and distance learning techniques that were effective for nursing awareness and education aimed at improving nursing care in diabetic patients were explored. At the same time, the impact of the work environment and the time spent by nurses on the content and the possibility of monitoring such programs. Results: Modern information and education technologies can lead to the creation of rich, easy-to-use and easy-to-use teaching material through which nurses will be taught and updated their knowledge on issues related to the care of patients with diabetes mellitus. Nurses themselves seem to have realized the necessity of continuing education. The renewal of knowledge and educational material on specific subjects such as diabetes mellitus and the possibility of collaboration and exchange of experiences among learners allow a greater correlation of learning with the actual problems and situations that trainees are called upon to face in the workplace the environment. Conclusions: Distance education offers health care professionals, especially nurses, an attractive and promising way of lifelong education and training.